Anti-Dopamine Receptor 2 Antibody-Positive Encephalitis in Adolescent - Dai, Xuejiao; Kuang, Lilu; Feng, Li; Yi, Xiaoping; Tang, Weiting; Liao, Qiao; Long, Xiaoyan; Wang, Junling; Li, Jing; Yang, Huan; Xiao, Bo; Li, Guoliang; et al. (Frontiers in Neurology, 2020)
Autoimmune encephalitic syndromes include mutism, somnolence, movement disorder, and behavioral, or psychiatric symptoms. When paired with bilateral basal ganglia lesions on magnetic resonance imaging, these support the diagnosis of basal ganglia encephalitis (BGE). BGE is a rare but distinct entity of putative autoimmune etiology, with specific basal ganglia inflammation and acute movement disorders. A previous study identified dopamine-2 receptors (D2R) antibody to be positive in most BGE children, indicating that the D2R antibody may trigger the downstream pathological process in BGE patients. The highest levels of D2R are found in the striatum, the nucleus accumbens, and the olfactory tubercle. D2R antibody-positive BGE is widely reported in children. Here we present a 17-year-old girl with a typical clinical feature of basal ganglia encephalitis, who benefited from immune therapy.